Tobacco or Healthy Children: The Two Cannot Co-Exist - Pattemore, Philip K. (Frontiers in Pediatrics, 2013)
Tobacco exposure increases mortality and morbidity of the fetus, the child, the adolescent, and their children in turn. Nearly half the children in the world are exposed. Smoking is not merely personal choice or personal responsibility; those subtle phrases undermine those who have no choice in the matter. Tobacco control must take a multi-pronged attack. Smoking cessation by adults in childbearing years must take centre stage of these efforts, because it is the only way to ensure a smoke-free environment for children. Smoke-free parents provide a role model for smoke-free young people, and erode the image of smoking as a desirable adult behaviour to emulate. Pediatricians and pediatric pulmonologists have a key role to play here. This goal will reduce morbidity and mortality among adults and children. Legislation regarding taxation, environments, tobacco constituents, product placement and display, packaging, and media education are all key to this core goal. Smokefree policy must be protected from attack based on trade agreements. Research is needed into more effective ways to attract and help people give up smoking, and into educating and re-deploying tobacco industry workers in emerging and developed countries.